Cellulose hydrogel-based biodegradable and recyclable magnetoelectric composites for electromechanical conversion. (15th December 2022) - Hu, Sanming; Zheng, Min; Wang, Qi; Li, Ling; Xing, Jun; Chen, Kun; Qi, Fuyu; He, Pengyu; Mao, Lin; Shi, Zhijun; Su, Bin; Yang, Guang
Abstract: Flexible electromechanical conversion devices have attracted enormous attention as energy harvesters and self-powered sensors in the fields of wearable electronics and robotics. However, current flexible devices composed of plastic polymers and metals suffer from non-degradability and limited recyclability. Herein, a biodegradable and recyclable hydrogel-based magnetoelectric (ME) composite is fabricated via introducing NdFeB magnetic particles and copper wires into the regenerated bacterial cellulose (rBC) hydrogel. The developed hydrogel-based ME composites can effectively convert the mechanical kinetic energy into electrical energy based on the principle of electromagnetic induction, which maximum voltage reaches 15 μV. In addition, degradation experiments are conducted in this work to demonstrate the hydrogel can be rapidly degraded within 3 h under the condition of enzyme and completely natural degraded within 49 days in water, respectively. Moreover, the left NdFeB particles and copper wires can be recyclable and reused for the same devices, leaving no environmentally hazardous electronic waste. Graphical abstract: A biodegradable and recyclable hydrogel-based magnetoelectric (ME) composite composed of regenerated bacterial cellulose (rBC) hydrogel, NdFeB magnetic particles and copper wires is fabricated, which can effectively convert the mechanical kinetic energy into the electrical energy based on the principle of electromagnetic induction and leave no environmentally hazardous electronic waste after completing the mission. Unlabelled Image